ANALISA DAMPAK LALU-LINTAS PENGEMBANGAN RS TELOGOREJO DI JL. K.H. AHMAD DAHLAN SEMARANG - Aziz Zahwan; Riko Firmanda Muslim; Bambang Riyanto; Epf. Eko Yulipriyono (Jurnal Karya Teknik Sipil, 2013)
Telogorejo Hospital is a hospital located in the city center (CBD) with a lot of activity around it, so the traffic is congested. Currently, the private hospital is under developing with targeted towards an international hospital. Therefore it is important to assess the impact of traffic caused by the development. At the beginning of the calculation, we evaluated the performance of intersections and roads around the site development. Then proceed with the calculation of estimated towing vehicle movement and percentage growth. Both were included in the analysis of the performance of intersections and roads no hotspot at the post opening. The method of analysis used is MKJI (Indonesia Jalan Capacity Manual) 1997 dedicated to vehicle traffic. From the analysis it is known that the existing conditions in 2012 was the performance of intersections and roads hotspot is still good. It can be seen from the value of DS was still below 0.75, the speed on the road is still higher than 20 kilometer per-hour, and delay at the no hotspot intersection is still less than 30 seconds / smp. At the time of its unveiling in 2014, there is a condition on the Anggrek intersection at workingday at morning peak hours its DS value greater than 0.75 is 0.88. While the results of the analysis of the long-term 5 years after opening in 2019, Anggrek intersection performance became much worse that is the highest DS value of 1,04, but the intersection Theresiana still good. Technical solutions to address the intersection of Anggrek at the opening is to provide non-permanent median on the major approach of limiting the right turn movement on each approach and also a straight movement in South Seroja approach. The median was installed as weekday morning peak hour. In the segment of Road Anggrek is made diversion parking from the road. While the solution to the current problems five years after opening is to install a non-permanent median at the Anggrek  intersection so there is no right turn movement on each approach and also the straight movement in South Seroja  approach. It also made a major widening in line at 1 m on each side and minor lane widening at 0.5 m in each side. Simpang Theresiana good condition at present, at the opening, as well as five years after opening no problems whatsoever so there is no meaningful treatment. It's just that every Sunday morning there is a market there for people who can not be predicted future conditions, thus requiring further research.